A study of single nucleotide polymorphisms of GRIN2B in schizophrenia from Chinese Han population. (6th September 2016) - Guo, Zhenming; Niu, Weibo; Bi, Yan; Zhang, Rui; Ren, Decheng; Hu, Jiaxin; Huang, Xiaoye; Wu, Xi; Cao, Yanfei; Yang, Fengping; Wang, Lu; Li, Weidong; et al.
Highlights: GRIN2B rs890 demonstrated significant difference between cases and controls. Results adjusted by confounding factors as age and sex remain positive. Rs890 and rs1806191 may form a haplotype and associated with schizophrenia. The GRIN2B might be associated with schizophrenia in Chinese Han population. Abstract: Schizophrenia is a severe and complex mental disorder with high heritability. There is evidence that mutations in the gene of Nmethyl-d -aspartate-type glutamate receptors (NMDAR) are associated with schizophrenia. GRIN2B encodes a subunit of NMDARs, and has been identified as a candidate gene for many psychiatric disorders, especially schizophrenia. In this study, we investigated whether single nucleotide polymorphisms (SNPs) in GRIN2B were associated with schizophrenia. Four SNPs (rs890, rs1806191, rs219872, rs172677) were genotyped in 752 schizophrenic patients and 846 healthy controls of the Chinese Han population. Our results indicate differences in allele and genotype frequencies of rs890 between case and control. These results were assessed by adapting different genetic models (codominant, dominant, recessive, overdominant, log-additive models). After controlling for confounding factors including sex and age, rs890 remained associated with schizophrenia. In addition, rs890 and rs1806191 were found to form a haplotype associated with schizophrenia. In summary, our results indicate that the GRIN2B SNP rs890 might be associated with schizophrenia in the Chinese Han population.